2019
DOI: 10.1115/1.4044621
|View full text |Cite
|
Sign up to set email alerts
|

Liquid State Machine to Generate the Movement Profiles for the Gait Cycle of a Six Degrees-of-Freedom Bipedal Robot in a Sagittal Plane

Abstract: In this paper, an approach based on a liquid state machine (LSM) to compute the movement profiles to achieve a gait pattern subject to different variations in its trajectory is presented. At the same time, the position of the zero moment point (ZMP) to determine the stability of the six degrees-of-freedom (6DOF) bipedal robot in the sagittal plane during the gait cycle is calculated. The system is constructed as a supervised machine learning model. The time series of the oscillating foot trajectory obtained by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…These techniques utilize a fixed, randomly generated network of neurons, known as a reservoir, to process input data and generate output. In Franco-Robles et al (2020), a method that utilizes a LSM to compute movement profiles has been proposed and they used a set of numerical experiments to validated the performance of their method. The results showed that the gait of the bipedal robot is stable in terms of the zero moment point (ZMP) when using the movement profiles generated by the LSM approach.…”
Section: Machine Learning Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…These techniques utilize a fixed, randomly generated network of neurons, known as a reservoir, to process input data and generate output. In Franco-Robles et al (2020), a method that utilizes a LSM to compute movement profiles has been proposed and they used a set of numerical experiments to validated the performance of their method. The results showed that the gait of the bipedal robot is stable in terms of the zero moment point (ZMP) when using the movement profiles generated by the LSM approach.…”
Section: Machine Learning Approachesmentioning
confidence: 99%
“…These techniques utilize a fixed, randomly generated network of neurons, known as a reservoir, to process input data and generate output. In Franco-Robles et al. (2020) , a method that utilizes a LSM to compute movement profiles has been proposed and they used a set of numerical experiments to validated the performance of their method.…”
Section: Introductionmentioning
confidence: 99%